Use of finger-prick dried blood spots (fpDBS) and capillary electrophoresis for carbohydrate deficient transferrin (CDT) screening in forensic toxicology - Bertaso, Anna; Sorio, Daniela; Vandoros, Anthula; De Palo, Elio F.; Bortolotti, Federica; Tagliaro, Franco (Electrophoresis, 2016)
Continued progress in chronic alcohol abuse investigation requires the development of less invasive procedures for screening purposes. The application of finger‐prick and related dried blood spots (fpDBS) for carbohydrate deficient transferrin (CDT) detection appears suitable for this aim. Therefore, the goal of this project was to develop a screening method for CDT using fpDBS with CZE analysis. Blood samples prepared by finger‐prick were placed on DBS cards and left to air dry; each dried fpDBS disc was shredded into small pieces and suspended in acid solution (60 μL of HCl 120 mmol/L). After centrifugation (10 min at 1500 × g), the collected sample was adjusted to pH 3.5. After an overnight incubation, the pH was neutralised and an iron rich solution was added. After 1 h, CZE analysis was carried out. A group of 47 individuals was studied. Parallel serum samples were collected from each investigated subject and the %CDT for each sample was measured using HPLC and CZE techniques. The fpDBS transferrin sialo isoform electropherograms were similar to those obtained with serum. Moreover, fpDBS CZE CDT percentage levels demonstrated significant statistical correlation with those obtained from serum for both HPLC and CZE %CDT (p < 0.01; r2 = 0.8913 and 0.8976, respectively), with %CDT from 0.8 to 13.7% for fpDBS and from 0.7 to 12.7% for serum. The newly developed fpDBS procedure for CDT analysis provides a simple and inexpensive tool for use in population screening.